A Food Bar Formulation Based on Local Soy Tempe Flour and Kepok Banana Flour: Food Bar - zesita devy 99, bemy cornellia (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Food bars are a type of food with high calories and are produced from various ingredients or are usually called blended food, are rich in nutrients, and are dense and compact. Food bars generally contain high levels of protein, carbohydrates, and fiber. As one application of the food diversification program, it is necessary to develop the production of food bars from local ingredients such as soybean tempeh and kepok bananas. This research aims to determine the differences in chemical and sensory characteristics of food bars with different formulations of soybean tempeh flour and kepok banana flour and to obtain a formulation that produces the best chemical and sensory characteristics. The research design used was a Randomized Block Design (RBD) with one factor (p), namely the formulation of soybean tempeh flour and kepok banana flour (p), which consisted of five levels and five repetitions. The research results showed that the formulation of tempeh flour and kepok banana flour influenced the water content, ash content, fat content, and protein content but did not affect the crude fiber content of the food bar produced. The formula that produces the best chemical and sensory characteristics is the formulation of tempe flour and kepok banana flour (45:55) with a water content of 12.66%, ash content of 2.44%, fat content of 31.64%, protein content of 18.90%, carbohydrate content 34.35%, crude fiber content 0.97%, color assessment 2.93 (dislike – like), taste 3.38 (like – like very much), aroma 2.70 (dislike – like), texture 3.30 (like – like very much), and overall liking 3.22 (like – like very much). Keywords : Protein, Fiber, Soy Tempeh Flour, Kepok Banana Flour, Tapioca, Food Bar